Photovoltaic Characterization of Dye-sensitized Solar Cells with Natural Dyes using Synthesized ZnO nanostructures - Karki, I. B.; Chatterjee, S.; Nakarmi, J. J.; Sinha, D.; Goswami, D.; Mandal, P. K. (Journal of Nepal Chemical Society, 2013)
Considerable attention was created over the past decade on Dye-sensitized solar cells (DSSCs) as a viable alternate technology for renewable energy. Much attention was attracted due to their high efficiencies and potentially low production costs. In this paper, DSSCs with natural dyes were successfully synthesized using ZnO nanostructures. ZnO nanorods were grown on an ITO coated glass using sol-gel method and used to fabricate DSSCs using natural dyes and liquid potassium iodide (KI3) electrolyte. Different natural dye were analyzed for its suitability to be used in DSSC and subsequently used to fabricate the cell. Finally the photovoltaic properties of the ZnO based DSSC samples were systematically analyzed. Roles of new sensitizer dye were investigated and the results were compared. The ZnO nanorods grown by the sol-gel method have more uniform thickness. The DSSC structure with Carbon counter electrode yields an open circuit voltage markedly higher from DSSC on an ITO glass and has energy conversion efficiency less than 2%. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9336 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 56-62 Uploaded date: 12/16/2013